FGF-23 and Phosphate in Children with Chronic Kidney Disease: A Cross-Sectional Study in Kazakhstan - ALPAY, HARİKA (MDPI, 2020)
Background and objectives: Chronic kidney disease (CKD) in children is a complex medical and social issue around the world. One of the serious complications is mineral-bone disorder (CKD-MBD) which might determine the prognosis of patients and their quality of life. Fibroblast growth factor 23 (FGF-23) is a phosphaturic hormone which is involved in the pathogenesis of CKD-MBD. The purpose of the study was to determine what comes first in children with CKD: FGF-23 or phosphate. Materials and Methods: This cross-sectional study included 73 children aged 2-18 years with CKD stages 1-5. We measured FGF-23 and other bone markers in blood samples and studied their associations. Results: Early elevations of FGF-23 were identified in children with CKD stage 2 compared with stage 1 (1.6 (1.5-1.8) pmol/L versus 0.65 (0.22-1.08), p = 0.029). There were significant differences between the advanced stages of the disease. FGF-23 correlated with PTH (r = 0.807, p = 0.000) and phosphate (r = 0.473, p = 0.000). Our study revealed that the elevated level of FGF-23 went ahead hyperphosphatemia and elevated PTH. Thus, more than 50% of children with CKD stage 2 had the elevating level of serum FGF-23, and that index became increasing with the disease progression and it achieved 100% at the dialysis stage. The serum phosphate increased more slowly and only 70.6% of children with CKD stage 5 had the increased values. The PTH increase was more dynamic. Conclusions: FGF-23 is an essential biomarker, elevates long before other markers of bone metabolism (phosphate), and might represent a clinical course of disease.
Keywords: fibroblast growth factor 23; parathyroid hormone; hyperphosphatemia; phosphate metabolism; mineral and bone disorder